A Study in Technical and Economic Indicators of Post-Tensioned Slabs Execution For Rise Buildings - Hassan, Bassam; Omran, Jamal; Fedda, Ali (Latakia University Journal -Engineering Sciences Series, 2020)
This research aims at highlighting the economic role and technical specifications, as well as the sustainable impact of using the Post-Tensioned Slab technology in the construction work, especially in the implementation of high buildings due to the urgent need to find a quick and economical construction alternatives, as well as decreasing the negative environmental impact as a result of horizontal urban expansion to agricultural areas, by supporting the vertical methods of sustainable construction, which lead to a professional execution level of high buildings in accordance with the latest technological and economic methods, and finding a practical solutions to the vertical expansion of cities. This study includes the technical characterization of the post-tensioned slab technology according to the latest international norms (State of Arts), and studying a high building with three alternatives of slabs construction (Flat Slab, Pt Slab, Drop Panel Slab), which gave exact operational indicators for the post-tensioned slabs through comparison with other alternatives. The results of the study showed a significant decrease in the usage of construction resources (Steel and concrete at 53.22% and 39.62%, respectively), as well as a decrease in the thickness of the slab with 25.93%. This study was based on the Ram Concept program for the design of post-tensioned slab, and (Revit & AutoCAD) programs in the architectural design and rise building quantities calculation for each of the three alternatives. يهدف هذا البحث إلى إبراز الدور الاقتصادي والمواصفات الفنية, وكذلك التأثير المستدام لاستخدام تقنية البلاطات اللاحقة الشد في أعمال البناء، لاسيما في تنفيذ الأبنية العالية نتيجة الحاجة الماسة إلى إيجاد بدائل تشييد سريعة واقتصادية، وتخفيض التأثير البيئي السلبي الناتج عن الزحف العمراني الأفقي إلى المناطق الزراعية, عبر دعم الطرائق الشاقولية للتشييد المستدام, مما يؤدي إلى رفع سوية تنفيذ الأبنية العالية وفقا لأحدث الطرائق التكنو اقتصادية, وإيجاد حلول عملية للتوسع الشاقولي للمدن السورية. تتضمن هذه الدراسة التوصيف الفني لتقنية البلاطات اللاحقة الشد وفقا لأحدث النورمات العالمية, وكذلك دراسة مبنى عال وفقا لثلاثة بدائل لتشييد البلاطات, وهي نظام البلاطة المنبسطة والبلاطة اللاحقة الشد والبلاطة المنبسطة مع سقوط (Drop Panel Slab, Pt Slab, Flat Slab), مما أعطى مؤشرات تنفيذية دقيقة للبلاطات اللاحقة الشد من خلال المقارنة مع البدائل الأخرى. اعتمدت هذه الدراسة على برنامج (Ram Concept) من اجل تصميم البلاطات اللاحقة الشد, وكذلك برنامجي (Revit & AutoCAD) في التصميم المعماري وحساب الكميات للمبنى العالي لكل من البدائل الثلاثة. بينت نتائج الدراسة انخفاض ملحوظ في استخدام موارد البناء(فولاذ تسليح و بيتون بنسبة53.22% و 39.62% على التوالي) وكذلك انخفاض سماكة البلاطة بنسبة 25.93 %.